2006
DOI: 10.1038/sj.ejcn.1602540
|View full text |Cite
|
Sign up to set email alerts
|

Malnutrition among gynaecological cancer patients

Abstract: Objective: To assess the nutritional status of patients with gynaecological cancer. Design: A prospective study assessing the nutritional status of gynaecological patients with suspected or proven gynaecological cancer. Setting: Queensland Centre for Gynaecological Cancer, Brisbane, Australia; a tertiary referral centre for gynaecological cancer. Subjects: One hundred forty-five patients with suspected or proven gynaecological cancer aged 20-91 years. Intervention: Scored patient-generated subjective global as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
123
3
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 135 publications
(139 citation statements)
references
References 24 publications
10
123
3
3
Order By: Relevance
“…In a study done in Queensland University of Australia in 2007 on 145 gynecological cancer patients who completed PG-SGA questionnaire, 80% were assigned well nourished and 20% to moderate malnutrition (Laky et al, 2007). No article or specific relevant study was found to be done in Iran or other under developed countries.…”
Section: Nutritional Assessment Of Cancer Patients In Tehran Iranmentioning
confidence: 99%
“…In a study done in Queensland University of Australia in 2007 on 145 gynecological cancer patients who completed PG-SGA questionnaire, 80% were assigned well nourished and 20% to moderate malnutrition (Laky et al, 2007). No article or specific relevant study was found to be done in Iran or other under developed countries.…”
Section: Nutritional Assessment Of Cancer Patients In Tehran Iranmentioning
confidence: 99%
“…Albumin and globulins play a pivotal role in the inflammatory process . Serum albumin is also an objective parameter that reflects the degree of long-term nutrition status (Laky et al, 2007). The globulins play an important role in immunity and chronic inflammation and reflects a cumulative exposure of different cytokines (Azab et al, records; (4) patient had complete follow-up data.…”
Section: Introductionmentioning
confidence: 99%
“…Albumin and globulins play a pivotal role in the inflammatory process . Serum albumin is also an objective parameter that reflects the degree of long-term nutrition status (Laky et al, 2007 …”
mentioning
confidence: 99%
“…Although it is well known that malnutrition is most prevalent in patients with gastric, lung, pancreatic, and colon cancer, the reported prevalence of malnutrition and related factors in gynecologic cancer varies [15][16][17][18]. Approximately 20-26 % of gynecologic cancer patients were found to have a nutritional disorder [13,16,18], while 50-67 % of ovarian cancer patients were reported to have a nutritional disorder [16,17].…”
Section: Introductionmentioning
confidence: 99%